Relationship between Canadian medical school student career interest in emergency medicine and post-graduate training disposition - Abu-Laban, Riyad; Scott, Ian; Gowans, Margot (Revue canadienne de l’éducation médicale, 2017)
Background: Canada has two independent routes of emergency medicine (EM) training and certification. This unique situation may encourage medical students with EM career aspirations to apply to family medicine (FM) residencies to subsequently acquire College of Family Physicians of Canada (CFPC) training and certification in EM. We sought answers to the following: 1) Are medical students who indicate EM as their top career choice on medical school entry, and then complete a FM residency, more likely to undertake subsequent CFPC-EM training than other FM residents who did not indicate EM as their top career choice; and 2) What are the characteristics of medical students in four predefined groups, based upon their early interest in EM as a career and ultimate postgraduate training disposition. Methods: Data were accessed from a survey of medical students in 11 medical school classes from eight Canadian universities and anonymously linked to information from the Canadian Residency Matching Service between 2006 and 2009. Results: Of 1036 participants, 63 (6.1%) named EM as their top career choice on medical school entry. Of these, 10 ultimately matched to a Royal College of Physicians and Surgeons of Canada (RCPSC) EM residency program, and 24 matched to a FM residency program, nine of whom went on to do a one-year CFPC-EM residency program in contrast to 57 of the remaining 356 students matching to FM residency programs who did not indicate EM was their top career choice (37.5% vs 16.0%, p=0.007). Statistically significant attitudinal differences related to the presence or absence of EM career interest on medical school entry were found. Conclusion: Considering those who complete CFPC-EM training, a greater proportion indicate on admission to medical school that EM is their top career choice compared to those who do not. Moreover, students with an early career interest in EM are similar for several attitudinal factors independent of their ultimate postgraduate training disposition. Given the current issues and challenges facing FM and EM, these findings have implications that merit consideration by both the CFPC and the RCPSC.